THE EFFECT OF THE SAVI LEARNING MODEL ON THE COGNITIVE LEARNING OUTCOME OF STUDENTS - Kusrini, Indar; Rintayati, Peduk; Salimi, Moh (Universitas Labuhanbatu, 2025)
Purpose – The cognitive learning outcomes of pupils are essential for assessing student progress and the quality of the implemented learning procedure. Nevertheless, the cognitive learning outcomes of students have not met expectations. This study aimed to assess the cognitive learning outcomes level of fourth-grade elementary pupils and the effect of the SAVI model on enhancing these cognitive learning outcomes.Methodology – The study method was quantitative, utilizing a quasi-experimental posttest-only control group design. The study's sample comprised 56 fourth-grade elementary school students. The selected data gathering method was a test. The assessment is structured as multiple-choice questions. This study utilized parametric statistical analysis to test hypotheses through the t-test. This study's research approach commences with planning, which includes identifying research subjects, conducting a literature review, acquiring research permits, and creating research instruments. In the implementation phase, the researcher delineates the experimental and control groups. Furthermore, after conducting several experiments, the researcher administered a post-test to the experimental and control groups. Following data collection, the researcher analyzed the defined problem and the established research objectives.Findings – This investigation indicated that most cognitive learning outcomes of pupils instructed through the SAVI learning model fell within the good category, and there was a significant disparity in cognitive learning outcomes between pupils instructed using the SAVI model and those receiving conventional instruction.Contribution – This study's results enhance students' cognitive learning outcomes.